Plasmonic Optoelectronic Memristor Enabling Fully Light‐Modulated Synaptic Plasticity for Neuromorphic Vision (Adv. Sci. 6/2022). Issue 6 (24th February 2022) - Shan, Xuanyu; Zhao, Chenyi; Wang, Xinnong; Wang, Zhongqiang; Fu, Shencheng; Lin, Ya; Zeng, Tao; Zhao, Xiaoning; Xu, Haiyang; Zhang, Xintong; Liu, Yichun
Abstract : Plasmonic Optoelectronic Memristors In article number 2104632, Zhongqiang Wang, Haiyang Xu, Yichun Liu, and co‐workers report a new type of plasmonic optoelectronic memristor for neuromorphic vision, in which the fully light‐modulated synaptic plasticity is demonstrated using visible and ultraviolet light stimulations. This memristor enables the combination of sensing and image pre‐processing functions in a single device, which may promote the future development of efficient neuromorphic vision.